Thermodynamic analysis of acetone sensing in Pd/AlGaN/GaN heterostructure Schottky diodes at low temperatures. (1st March 2016) - Das, Subhashis; Majumdar, Shubhankar; Kumar, Rahul; Ghosh, Saptarsi; Biswas, Dhrubes
Abstract: An AlGaN/GaN heterostructure based metal–semiconductor–metal symmetrically bi-directional Schottky diode sensor structure has been employed to investigate acetone sensing and to analyze thermodynamics of acetone adsorption at low temperatures. The AlGaN/GaN heterostructure has been grown by plasma-assisted molecular beam epitaxy on Si (111). Schottky diode parameters at different temperatures and acetone concentrations have been extracted from I–V characteristics. Sensitivity and change in Schottky barrier height have been studied. Optimum operating temperature has been established. Coverage of acetone adsorption sites at the AlGaN surface and the effective equilibrium rate constant of acetone adsorption have been explored to determine the endothermic nature of acetone adsorption enthalpy. Graphical abstract: